Limites e evolução geodinâmica do Sistema Jaguaribeano, Província Borborema, Nordeste do Brasil - Cavalcante, José Carvalho (1999)
The studied area is geologically located in the Northern Domain of the Borborema Province (Northeast Brazil), limited to the south by the Patos shear zone. Terranes of the Jaguaribeano system are dominant, flanked by the Piranhas (E and S sides) and Central Ceará (NE side) terranes. Its basement comprises gneiss -migmatite terrains of Paleoproterozoic to Archean age (2.6 to 1.9 Ga old), overprinted by neoproterozoic to cambrian tectonotherma l events. Narrow supracrustal belts ( schist belts) display a 1.6 to 1.8 Ga age, as shown by whole - rock Rb-Sr and zircon U-Pb and Pb/Pb dates in acid metavolcanics which dominate in the lower section of these sequences, and in coeval metaplutonics (granitic augen gneisses). From the stratigraphic point of view, three Staterian belts are recognized: 1. Orós Belt - made up by the Orós Group, subdivided in the Santarém (predominantly pure to impure quartzites, micaschists and metacarbonates) and Campo Alegre (metandesites, metabasalts, metarhyolites and metarhyodacites, interlayered with metatuffs and metasediments) formations, and by the Serra do Deserto Magmatic Suite (granitic augen gneisses). 2. Jaguaribe Belt - its lithostratigrahic-lithodemic framework is similar to the one of the Orós Belt, however with a greater expression of the volcano -plutonic components (Campo Alegre Formation and Serra do Deserto Magmatic Suite). The Peixe Gordo Sequence, separately described, is also related to this belt and contain s metasedimentary, metavolcanic (with subordinated volcanoclastics) and metaplutonic units. The first one correlated to the Orós Group and the latter the Serra do Deserto Magmatic Suite. 3. Western Potiguar Belt - represented by the Serra de São José Gro up, subdivided in the Catolezinho (biotite -amphibole gneisses with intercalations of metacarbonates, calcsilicate rocks, amphibolites and quartzite beds to the top) and Minhuins (quartzites, micaschists, metaconglomerates, calcsilicate rocks, acid to the b asic metavolcanics and metatuffs) formations. Its late Paleoproterozoic (Staterian) age was established by a Pb/Pb date on zircons from a granitic orthogneiss of the Catolezinho Formation. The petrographic characteristics and sedimentary structures of the Santarém Formation of the Orós Group point to deltaic to shallow marine depositional systems, overlain by deep water deposits (turbidites). The geodynamic setting of this region encompassed a large depositional basin, probably extending to the east of the Portalegre shear zone and west of the Senador Pompeu shear zone, with possible equivalents in the Jucurutu Formation of the Seridó Belt and in the Ceará Group of central Ceará. The Arneiróz Belt, west Ceará, displays some stratigraphic features and granito ids geochemically akin to the ones of the Orós Belt. The evolutionary setting started with an extensional phase which was more active in the eastern part of this domain (Western Potiguar and part of the Jaguaribe belts), where the rudite and psamite sedime ntation relates to a fluviatile rift environment which evolved to a prograding deltaic system to the west (Orós Group). The basaltic andesitic and rhyolitic volcanics were associated to this extensional phase. During this magmatic event, acid magmas also crystallized at plutonic depths. The Orós Group illustrates the environmental conditions in the western part of this domain. Later on, after a large time gap (1.6 to 1.1 Ga), the region was subjected to an extensional deformational episode marked by 900 Ma old (Sm-Nd data) basic rocks, possibly in connection with the deposition of the Cachoeirinha Group south of the Patos shear zone. In the 800 to 500 Ma age interval, the region was affected by important deformational and metamorphic events coupled with in trusion of granitic rocks of variable size (dykes to batholiths), related to the Brasiliano/Pan -African geotectonic cycle. These events produced structural blocks which differentiate, one from the other, according to the importance of anatectic mobilizatio n, proportion of high-grade supracrustals and the amount of neoproterozoic -cambrian granitoid intrusions. On this basis, a large portion of the Jaguaretama Block/Terrane is relatively well preserved from this late overprint. The border belts of the Jagua retama Block (Western Potiguar and Arneiroz) display kyanite-bearing (medium pressure) mineral associations, while in the inner part of the block there is a north-south metamorphic zoning marked by staurolite or sillimanite peak metamorphic conditions. Regarding the deformations of the Staterian supracrustal rocks, second and third phases were the most important, diagnosed as having developed in a progressive tectonic process. In the general, more vigorous conditions of PT are related to the interval tardi - phase 2 early-phase 3, whose radiometric ages and regional structuring indicators places it in the Brasiliano/Pan-African Cycle. In the Staterian geodynamic setting of Brazilian Platform , these sequences are correlated to the lower Espinhaço Supergroup (p.ex., Rio dos Remédios and Paraguaçu groups, a paleproterozoic rift system in the São Francisco Craton), the Araí and Serra da Mesa groups (north of Goiás, in the so -called Goiás Central Massif), and the Uatumã Group (in the Amazonian Craton). Granitic ( augen gneisses) plutonics are also known from these areas, as for example the A-type granites intrusive in the Araí and Serra da Mesa groups, dated at 1.77 Ga. Gravimetric and geological data place the limits of the Jaguaribeano System (terranes) along the Senador Pompeu Shear Zone (western border) and the Portalegre- Farias Brito shear zone (eastern and southern). However, the same data area not conclusive as regards the interpretation of those structures as suture of the terrane docking process. The main features of those shear zones and of involved lothological associations, appear to favour an intracontinental transpressional -transcurrent regime, during Neoproterozoic-Cambrian times, marking discontinuities along which different crustal blocks were laterally dispersed. Inside of this orogenic system and according to the magnetic data (total field map), the most important terrane boundary appears to be the Jaguaribe shear zone. The geochronological data, on some tectonostratigraphic associations (partly represented by the Ceará and Jucurutu groups), still at a preliminary level, besides the lack of granitic zonation and other petrotectonic criteria, do not allow to propose tectonic terrane assembly diagrams for the studied area